Power Factor Improvement in Power System with the Integration of Renewable Energy - Sim, S.Y.; Goh, H.H.; Lim, A. J. M. S.; Buswig, Y. M. Y.; Kek, S.L.; Mustafa, F.; Bohari, A.; Ardi, M. A. (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
The non-linear constant increment of power demands due to loads caused a complexity in the operation of the power system network and might also cause insecurity without adequate control in the system with large power flows. A successful alternative energy source gives new challenges when connected to the power grid system. It is however that with the presence of environmental conditions, there is a constant fluctuation of generated power from renewable energy sources. This can be explained when wind power is used as a source of injection into an electric grid, where the power quality will be affected due to the fluctuating condition of the nature of the wind and comparatively new types of its generators panel. Power system control is introduced in this matter using a controller known as FACTS (Flexible AC Transmission System). FACTS controllers such as STATCOM (Static Synchronous Compensator) and SSSC (Static Synchronous Series Compensator) can function to be a terminal voltage regulator to the power system and consequently improve the systems’ stability and power quality. With the usage of IEEE 14 bus power system network, both the potential STATCOM and SSSC are measured using the controller at high influential locations of the power system.